Lateral PIN Photodiode with Germanium and Silicon Layer on SOI Wafers - Silva, Fábio A. [UNESP]; Doria, Rodrigo T.; Simoen, E.; Andrade, M. G.C. [UNESP] (Journal of Integrated Circuits and Systems, 2023)
It has been verified through numerical simulations calibrated to experimental data the changes that the insertion of a germanium layer can bring to the electrical power generation of a silicon solar cell. The insertion of a germanium layer on top or below a silicon PIN diode designed in SOI technology has been considered. Results showed that different semiconductor characteristics (bandgap, mobility, and absorption coefficients) result in a general improvement in the solar cell performance, being able to reach a power 136% greater than the device without the heterogeneous layer. In the evaluated device the average power was improved from 9.43 nW to 14.92 nW with the Ge layer insertion. Besides that, the analysis has allowed for a better understanding of the phenomena that occur in the photogeneration of a cell with a heterojunction between germanium and silicon.
Keywords: Germanium; Heterojunction; PIN Diodes; SOI; Solar cells